Hi, I've gotten Spivak's calculus and I have a question on the second proof in the first chapter(adsbygoogle = window.adsbygoogle || []).push({});

What is wrong with the following "proof"?

suppose x=y

1. x² = xy

2. x² - y²= xy - y²

3. (x + y)(x - y)=y(x - y)

4. x + y=y

5. 2y = y

6. 2 = 1

I just want to clarify that the error is in the transition from step three to step four as subtracting both sides by (x - y) is to subtract by zero as if x=y then x -y = 0.

Step two is also saying that 0 = 0.

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Spivak 2=1 Proof fallacy

**Physics Forums | Science Articles, Homework Help, Discussion**